Managing social and environmental activities: toward sustainability of companies - Peni Nugraheni; Arum Indrasari; Noradiva Hamzah; Ruhanita Maelah (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2020)
Company's contribution to community through social activities and participations in protecting the environment gets more attention from the society. Similarly, the awareness of the company to contribute to the welfare of the community is also increasing. The paper aims to describe the importance of Corporate Social and Environmental Activities (CSEA) and the strategy of the company in managing and reporting CSEA. The sources of the data in this study were the secondary data from the previous literature, annual reports, and sustainability reports of the companies which were analyzed regarding to their implementations of CSEA. Some actions need to be planned by the companies to maximize their contributions to society through CSEA; among others are allocation of specific funds, establishment of specific department or division to manage CSEA, formulation and implementation of CSEA, disclosure and monitoring of CSEA. CSEA and its implementation report can influence the sustainability of company because the stakeholders will have positive appraisal to the company. This study is expected to provide an overview on the management of CSEA as a form of corporate social responsibility in improving the welfare of the community.